Community colleges and STEM : examining underrepresented racial and ethnic minorities - Palmer, Robert T.; Wood, J. Luke, 1982- (New York : Routledge, 2013)
"As United States policymakers and national leaders are increasing their attention to producing workers skilled in science, technology, engineering, and mathematics (STEM), community colleges are being called on to address persistence of minorities in these disciplines. In this important volume, contributors discuss the role of community colleges in facilitating access and success to racial and ethnic minority students in STEM. Chapters explore how community colleges can and do facilitate the STEM pipeline, as well as the experiences of these students in community college, including how psychological factors, developmental coursework, expertiential learning, and motivation affect student success. Community Colleges and STEM ultimately provides recommendations to help increase retention and persistence. This important book is a crucial resource for higher education institutions and community colleges as they work to advance success among racial and ethnic minorities in STEM education. "--
pt. 1. Pathways to success : the role of community colleges in promoting access to minorities in stem -- pt. 2. A new dimension to the discourse on minority students, stem, and community colleges -- pt. 3. Examining the experiences of minority students in community colleges : diverse contexts.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Science -- Study and teaching (Higher) -- United States; Technology -- Study and teaching (Higher) -- United States; Engineering -- Study and teaching (Higher) -- United States; Mathematics -- Study and teaching (Higher) -- United States; Science students -- United States; Community college students -- United States; Minority college students -- United States; Electronic books